Search for Narrow Hγ Resonances in Proton-Proton Collisions at √s = 13 TeV - Cms, Collaboration; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Dragicevic, M.; Erö, J.; Escalante Del Valle, A.; Flechl, M.; et al. (Karlsruhe, 2019)
A search for heavy, narrow resonances decaying to a Higgs boson and a photon (Hγ) has been performed in proton-proton collision data at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb-1 collected with the CMS detector at the LHC in 2016. Events containing a photon and a Lorentz-boosted hadronically decaying Higgs boson reconstructed as a single, large-radius jet are considered, and the γ+jet invariant mass spectrum is analyzed for the presence of narrow resonances. To increase the sensitivity of the search, events are categorized depending on whether or not the large-radius jet can be identified as a result of the merging of two jets originating from b quarks. Results in both categories are found to agree with the predictions of the standard model. Upper limits on the production rate of Hγ resonances are set as a function of their mass in the range of 720-3250 GeV, representing the most stringent constraints to date.

Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro (FAPERJ)

Centre National de la Recherche Scientifique
Keywords: Physics and Astronomy (all); Particle Physics; LHC; Higgs-Gamma Resonances; Physics Beyond Standard Model; CMS; Physics; ddc:530; info:eu-repo/classification/ddc/530; CMS, Higgs; Physics, LHC, CMS; High Energy Physics - Experiment